IMPACTS OF DEFORESTATION ON SOME SELECTED COMMUNITIES IN DAMATURU, YOBE STATE NIGERIA - Hassan Gana, Abdullahi; Sa'id, A. I. (FUDMA JOURNAL OF SCIENCES, 2022)
The study was carried out to assess the impacts of deforestation on some selected communities in Damaturu, Yobe State Nigeria. The study evaluated the main causes of deforestation in the study area. It also evaluated the effect of deforestation and its impact on the people of the area. A total of 150 questionnaires were administered to the participating households, purposive sampling techniques were used in generating primary data through questionnaire, discussion and observation and the data obtained were analyzed with descriptive statistics. Majority of the respondent (59.3%) were between the ages brackets of 31-40 years. The result of the study showed that 96 of the respondents representing 64.0% have strongly agreed believed deforestation are naturally occurrence. It also showed that 87 respondents representing 58.0% agreed that most logging for fuel wood is tremendously a major cause of deforestation. The findings of the research showed that most of the respondents have little knowledge of the consequences of deforestation. It was also found out that the main economic activities of the indigenes were farming, logging, which resulted in destroying large areas of land because they do not take any measures to conserve the forest in search of their basic daily needs. The study recommends that enforcement enacted against logging, education/awareness creation on effects of deforestation, re-introduction of tree planting programs, nurseries should be established in each of the communities to enable them raise seedlings for planting